A Malaysian consensus report on the diagnosis and treatment of Helicobacter pylori infection - Goh, Khean Lee; Lee, Yeong Yeh; Leow, Alex Hwong Ruey; Raja Affendi, Raja Ali *; Ho, Shiaw Hooi; Sanjiv, Mahadeva; Rosaida Hj, Mohd Said; Raman, Muthukaruppan Chettiar; Tee, Hoi Poh (Wiley, 2023)
Helicobacter pylori is one of the most common chronic bacterial infections in humans and responsible for 90% of duodenal ulcers and 70–90% of gastric ulcers. Despite this, many misconceptions regarding the appropriate diagnostic method and treatment strategies still exist in the Malaysian clinical practice. Under the initiative of the steering committee, an expert panel consisting of nine key opinion leaders in the field of gastroenterology convened to develop a set of consensus statements that are relevant to the Malaysian healthcare practice. The panel members reviewed the current evidence on the management of H. pylori infection, focusing on the best practices that are relevant to the Malaysian population based on clinical experience and published clinical evidence. Using the modified Delphi method, the panel achieved consensus in three areas of H. pylori infection management: indications for testing, diagnosis, and treatment. The panel proposed a set of 19 consensus statements, which were synthesized via two rounds of blinded voting and group discussions. The recommendations provided are relevant to the Malaysian population and can be used as a guide by physicians across various healthcare settings to facilitate appropriate diagnostic testing and treatment of H. pylori infection.